Australian journal of maritime and ocean affairs
AJMOA is a multidisciplinary journal that addresses the wide range of maritime issues, with a particular interest in Australia and the Indo-Pacific region. The materials published include articles dealing critically with some aspect of maritime affairs as well as shorter commentaries and casenotes on topical issues of marine or maritime interest.